Pengaruh Disiplin Kerja, Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan pada CV Optik Aini di Sragen - Ismaylia Nila Affanti; Asih Handayani (STIKes Ibnu Sina Ajibarang, 2024)
The problem in this research is whether there is a significant influence of work discipline, compensation and motivation on employee performance. The aim of this research is to analyze the significance of the influence of work discipline, compensation and work motivation on employee performance. The type of data used is quantitative. The data source used is primary data. The sampling technique used was purposive sampling with a total of 30. Data collection techniques in this research used observation, questionnaires and literature study. The research results show that the work discipline variable has a positive and significant effect on employee performance, the compensation and work motivation variables have an insignificant effect on employee performance.